Effect of Nitrogen and Potassium on the Root Growth, Nutrient Content and Yield of Mungbean (Vigna radiata L. Wilczek) under Waterlogged Condition (The Agriculturists, 2016)
An experiment was conducted with mungbean genotype IPSA-13 in the field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during September, 2012 to November, 2012 to study the root growth, nutrient concentration and seed yield of mungbean as influenced by N and K under waterlogged conditions. Nutrient supply in the soil had significant impact on better recovery in root development of 4-day waterlogged plants. Development of adventitious roots was one of the adaptive responses of IPSA-13 mungbean genotype. Root length was decreased due to the anaerobic condition.  Plants waterlogged for 4-days allocated more dry matter in adventitious root development and hence root volume was higher in waterlogged plants. Root volume in flooded plants increased due to the development of adventitious roots. Root dry weight increased with combined application of N and K fertilizers. Flooded plants treated with 14 kg N ha-1 + 25 kg K ha-1 produced the highest TDM and seed yield, though the yield was statistically similar to that obtained when the levels of N and K were applied separately, as well as with that of 1% urea + 25 kg K ha-1.The Agriculturists 2015; 13(1) 67-78